(untitled) (Al-Academy, 2024)
The theatrical performance embodies a multi-faceted aesthetic taste that has emerged from the creative human consciousness. As human thinking evolved and developed a love for play and entertainment, it began to fill its aspects with singing, acting, shaping, and decorating. The basics of this study consist of the primary form of theatrical performance and its symbols, meanings, and the use of children’s theater in efforts to achieve visual and kinetic events through harmony and development of various means until it became the fundamental and essential role in using the actor’s tools as a tangible sign and nucleus in the formation of the theatrical performance. This medium is especially true when the theatrical act gains a diverse aesthetic formation to entertain and delight children. Therefore, the researcher presented his study entitled "Aesthetics of Theatrical Performance Formation in Children’s Theater (Jad and Yara in the World of Arts - Model)" in the light of four chapters according to the scientific research methodology, seeking to achieve the research goal of revealing the aesthetics of the formation of theatrical performance in the Jad and Yara in the World of Arts play. The study concluded with several results, the most important of which is that the aesthetics of theatrical performance were characterized by diversity, repetition, and change of visual forms, the use of kinetic performance of visual and auditory elements, and its intellectual and aesthetic significance. In addition, the consistent color harmony, in which the theatrical performance formed an interactive product, was a dynamic organization in which balance and form were transferred.